Peran Moderasi Manajemen Risiko Perusahaan Terhadap Hubungan Antara Aktivitas Pendanaan Eksternal Dengan Manajemen Laba - Bayu Fajar Rianto; Faisal Faisal (Jurnal Akademi Akuntansi, 2022)
This study examines the relationship between a company's external financing activity and earnings management and enterprise risk management as moderation variable. The sample of the study was 271 companies listed in the Bloomberg database in 2018. The results of this study show that: First, external financing activities of both debt and equity are positively associated with accrual earnings management and real activity earnings management. Second, enterprise risk management has a significant influence on the relationship between external funding activities and earnings management. The results of this study make a significant contribution to stakeholders to strength managers to augment the company's risk management functions in an effort to prevent earnings management practices.